A novel strategy to boost the oxygen evolution reaction activity of NiFe-LDHs with in situ synthesized 3D porous reduced graphene oxide matrix as both the substrate and electronic carrier. (8th April 2019) - Gu, Yanfang; Wang, Yuanqiang; An, Wei; Men, Yong; Rui, Yichuan; Fan, Xinyi; Li, Bin
Abstract : NiFe-LDHs anchored on a 3D rGO matrix achieved a small overpotential and a relatively stable operating potential. Abstract : A novel strategy to boost the oxygen evolution reaction (OER) activity of NiFe-LDHs has been developed using reduced graphene oxide (rGO) as both the substrate and electronic carrier. Basically, a GO hydrogel is printed on Ni foam by the doctor blade technique, forming a GO matrix embedded in Ni foam, which is then freeze-dried to turn into a 3-dimensional (3D) porous GO (3D-GO) matrix. NiFe-layered double hydroxide (NiFe-LDH) nanoflakes anchored on the 3D-GO matrix embedded in Ni foam are synthesized by a hydrothermal process, together with the in situ reduction of 3D-GO. The obtained electrode has a high degree of reduction of the porous graphene oxide, the mechanical strength of the NiFe-LDH nanoflakes anchored on the matrix, large active surface area and excellent interface conjunction. Based on optimal conditions, the fabricated electrode shows outstanding electrocatalytic oxygen evolution reaction performance in 1 M KOH aqueous solution, achieving a small overpotential of 170 mV, a Tafel slope of 57 mV decade −1 at a current density of 20 mA cm −2 and a relatively stable operating potential after 2000 cycles of the CV test.